2018
DOI: 10.2166/wh.2018.164
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of free-living amoebae (Acanthamoeba, Balamuthia, Naegleria) in water samples in Peninsular Malaysia

Abstract: The aim of this study was to determine the occurrence of free-living amoebae (FLA) in Peninsular Malaysia and to compare different methodologies to detect them from water samples. Water samples were collected from tap water, recreational places, water dispensers, filtered water, etc. and tested for FLA using both cultivation and polymerase chain reaction (PCR) via plating assays and centrifugation methods. Amoebae DNA was extracted using Instagene matrix and PCR was performed using genus-specific primers. Of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 35 publications
1
3
0
1
Order By: Relevance
“…Similar results have been reported in Egypt (20,21,23) and Spain (22). Additionally, in Malaysia, Gabriel et al (24) showed that 64% of isolated FLA by culture method were positive as…”
Section: Outsupporting
confidence: 79%
“…Similar results have been reported in Egypt (20,21,23) and Spain (22). Additionally, in Malaysia, Gabriel et al (24) showed that 64% of isolated FLA by culture method were positive as…”
Section: Outsupporting
confidence: 79%
“…Consistent with this study, N. fowleri was frequently detected relative to Acanthamoeba spp. by PCR molecular technique in untreated and treated water [57], tap water [58], and from municipal drinking waters and recreational water sources [59]. This work presented herein demonstrated that L. micdadei and L. bozemanii were more often related to N. fowleri than Acanthamoeba spp., and the correlation between these species in the building water system and cooling towers observed separately (data not shown) could be due to the microbes being released into the water column from sloughing of the biofilms.…”
Section: Discussionmentioning
confidence: 60%
“… Poor et al ( 2018 ) Iran Swimming pool and hot tubs (10) 40 8 Morphology, PCR Acanthamoeba T3 and Acanthamoeba T4 Vijayakumar ( 2018 ) Saudi Arabia Pools and recreation waters 27 7 Morphology Acanthamoeba spp. Xue et al 2018 USA lake recreation areas (10) 160 56 PCR N. fowleri Gabriel et al 2019 Malaysia Recreational place 57 40 Morphology, PCR Acanthamoeba spp. and Naegleria spp.…”
Section: Resultsmentioning
confidence: 99%